(untitled) (Global Journal of Management and Business Research, 2018)
The paper focuses on the role of Bangladesh government in promoting Corporate Social Responsibility (CSR) in the country’s Ready-Made Garment (RMG) industry. Based on the four public policy roles proposed by Fox, Ward, and Howard (2002), this paper investigates the point to which the Bangladesh government has facilitated or initiated CSR practices in the selected sector. It reveals that since 2013, the government has taken various noteworthy initiatives from the perspectives of policy formulation, creating enabling environment for practicing CSR, instigating social dialogues, supporting stakeholder engagement, etc. However, it is urgent to adopt measures so that firms get recognition of their positive initiatives and become concerned to violate or ignore the government rules.